Research progress of organic liquid electrolyte for sodium ion battery - Zhang, Jia; Li, Jianwei; Wang, Huaiyou; Wang, Min (Frontiers in Chemistry, 2023)
Electrochemical energy storage technology has attracted widespread attention due to its low cost and high energy efficiency in recent years. Among the electrochemical energy storage technologies, sodium ion batteries have been widely focused due to the advantages of abundant sodium resources, low price and similar properties to lithium. In the basic structure of sodium ion battery, the electrolyte determines the electrochemical window and electrochemical performance of the battery, controls the properties of the electrode/electrolyte interface, and affects the safety of sodium ion batteries. Organic liquid electrolytes are widely used because of their low viscosity, high dielectric constant, and compatibility with common cathodes and anodes. However, there are problems such as low oxidation potential, high flammability and safety hazards. Therefore, the development of novel, low-cost, high-performance organic liquid electrolytes is essential for the commercial application of sodium ion batteries. In this paper, the basic requirements and main classifications of organic liquid electrolytes for sodium ion batteries have been introduced. The current research status of organic liquid electrolytes for sodium ion batteries has been highlighted, including compatibility with various types of electrodes and electrochemical properties such as multiplicative performance and cycling performance of electrode materials in electrolytes. The composition, formation mechanism and regulation strategies of interfacial films have been explained. Finally, the development trends of sodium ion battery electrolytes in terms of compatibility with materials, safety and stable interfacial film formation are pointed out in the future.